Pengembangan Aplikasi Pelaporan Informasi Bencana Kebakaran di Jakarta Timur Berbasis Android - Farah Alysia Parahita; Ester Lumba (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an application for providing information on Android disasters in East Jakarta with the Android operating system. The Android fire alarm application can report events based on the current location connected to the Internet and connected to the Global Positioning System (GPS). The application reporting can display the reporter's current location on a map and can report fire information. The application development method used is the Unified Rational Process (RUP) with Unified Modeling System (UML) modeling. The application development process using the Android Studio IDE. In addition, this application was built using the programming languages ​​PHP, HTML, Javascript, and using MySQL as a database.